Multiletramentos mediados pelo computador em sala de aula: a perspectiva das culturas juvenis em fluxo - Cavalcante, Andrea Pinheiro Paiva (2014)
The research takes as its starting point the uses of laptops in the classroom, from Project One Computer per Student in the Middle and High School Flor de Maravilha in Fortaleza. Through an ethnographic approach (CLIFFORD, 2002; GEERTZ, 1989; DAMATTA, 1978; ANDRÉ, 2010, 1995), with multifaceted character (ARDOINO, 1995) we seek to listen the constellations of experiences that make up such “events multiliteracies” at school when youth cultures deal with digital and communication technologies to answer the question: how the use of laptop, in the context of school, fosters youth multiliteracies experiences? Were taken as units of analysis, “events of multiliteracies” involving reading situations, writing and photographic production, performed in 2013 in the 6th grade classes. The theoretical framework presents the main aspects Pedagogy of Multiliteracies (NEW LONDON GROUP, 1996; COPE; KALANTZIS, 2009; ROJO, 2012; 2013) and Youth Cultures (PAIS, 2003). For Pedagogy of Multiliteracies is necessary to articulate, in the learning process, the multiplicity of communication media and the cultural and linguistic diversity of students, recognizing their subjectivities. In view of the studies of Youth Cultures, the modes of being young are composed of multiple forms, whether in relations between peers, language, ways of dressing and behaving, which vary according to the socio-economic conditions of youths. The contribution of Mead (2006) is central to understanding that prevails in contemporary pre-figurative culture whose hallmark is the fact that adults learn from children, unlike the primitive cultures, post - figurative, where knowledge was transmitted from older to younger. The analysis of "events of multiliteracies" pointed, among other things, the importance of recognizing that new ways of learning are made possible by the use of computers in the classroom, from the dimensions of "contextualized learning" and "transformative practice" proposals by the Pedagogy of Multiliteracies; the computer in the classroom needs to be seen more as a social practice rather than technology (Rodrigues, 2009) and which is necessary to overcome the belief that children have an innate competence to deal with the technological artifacts (FANTIN, 2012; BUCKINGHAM , 2007).